Co-identifying collective investment models for solar-based irrigation bundles in Northern Ghana - Ofosu, Abena; Minh, Thai Thi; Dickson, Desire Naab; Okem, A. E.; Barry, I.; Schmitter, Petra (International Water Management Institute, 2025)
Collective action among smallholder farmers enhances resource mobilization and addresses challenges beyond individual capacity. In Northern Ghana, farmers collaborate in formal and informal groups to strengthen their farming activities. While collective investment in irrigation has improved yields, income, and nutrition, the solar-based irrigation supply chain often overlooks farmer groups and cooperatives. To address this gap, this study applies a mixed-method analysis of collective investment models in solar-based irrigation bundles (SBIBs). Collective irrigation investment (CI-in) is a form of collective action by farmer-based organizations, involving voluntary risk-taking to achieve shared irrigation goals. CI-in supports cost-sharing, commercialization of irrigated farming, and better access to resources, technical assistance, and market information (Filippi et al. 2022). SBIBs integrate core products (e.g., solar pumps, boreholes, water application equipment), financial services (e.g., pay-as-you-go/ pay-as-you-own: PAYGO and PAYOWN are financial services designed to reduce upfront investment costs for farmers. PAYOWN allows farmers to buy solar-powered irrigation pumps through flexible installment plans until full ownership is achieved, whereas PAYGO provides water access on credit, with the pump operating only when payments are made, digital payments, tailored business models, sales and service networks), complementary services (extension, capacity strengthening, market linkages, storage and processing facilities), and scaling actions to meet diverse farmer needs.